2011
DOI: 10.1080/15377938.2011.594363
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Inclusion: Black Political Incorporation and the Use of Lethal Force

Abstract: Scholarship on the incorporation of Blacks in government andpolitics has focused on electoral gains and representational styles, but the broad, substantive benefits of inclusion have yet to be established. Utilizing data from 1994 to 2004 for 30 of the 60 largest U.S. cities, random-effects negative binomial regressions for panel data show that the political incorporation of Black elected officials reduces the likelihood of the incidence of lethal force over time, with significance reaching the .01 level in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…The coefficient on the share of black officers is negative and statistically significant at the 5 percent level, though the coefficient for the share of Hispanic officers in a department is not statistically significant. The negative and significant coefficient for the share of black officers is consistent with Legewie and Fagan (2016) and Nicholson-Crotty et al (2017), but at odds with Smith (2003) and Ochs (2011). Because the diversity of the overall police force is likely correlated with the chances that a department will have a nonwhite police chief, I enter the following variables into the regression in column 3: share of black officers, share of Hispanic officers, and indicators for a black police chief and a Hispanic police chief.…”
Section: Data Sources and Methodologysupporting
confidence: 78%
See 1 more Smart Citation
“…The coefficient on the share of black officers is negative and statistically significant at the 5 percent level, though the coefficient for the share of Hispanic officers in a department is not statistically significant. The negative and significant coefficient for the share of black officers is consistent with Legewie and Fagan (2016) and Nicholson-Crotty et al (2017), but at odds with Smith (2003) and Ochs (2011). Because the diversity of the overall police force is likely correlated with the chances that a department will have a nonwhite police chief, I enter the following variables into the regression in column 3: share of black officers, share of Hispanic officers, and indicators for a black police chief and a Hispanic police chief.…”
Section: Data Sources and Methodologysupporting
confidence: 78%
“…There is some conflicting evidence on the effect of racial composition and diversity of the police force on police violence. Smith (2003) finds no effect of the racial composition of a police force and its incidence of police killings of felons, while Ochs (2011) shows that rates of lethal force are higher when the proportion of black officers in a department increases. In research by Legewie and Fagan (2016), a more diverse police force reduces the rates at which blacks are killed by police officers.…”
mentioning
confidence: 99%
“…In some cases, studies have confirmed the finding that hiring more minority officers does not correlate with a reduction in the killing of citizens (see, e.g., Holmes and Smith ; Smith and Holmes ). Alternatively, some work has shown that the use of lethal force increases with the proportion of black officers (Ochs ). Finally, other studies have found that white officers are more likely to use deadly force than their black or Hispanic counterparts (see, e.g., McElvain and Kposowa ).…”
Section: Literature On Police Force Demographicsmentioning
confidence: 99%
“…However, there is also research that has found in general, minority officers can be harsher towards people of color based on deployment practices, struggling to fit in primarily white departments, or seeing themselves different from the people they policed (Alex, 1969; Dulaney, 1996; Heyman, 2002). Due to problems with reporting police shootings, it was not entirely clear whether Black officers had a higher rate of shootings than white officers (Ochs, 2011; Smith, 2003). In one of first research studies focusing on officer involved shootings and military status, Reingle Gonzalez et al.…”
Section: Overview Of Police Violence and The Importance Of Scholarly Activismmentioning
confidence: 99%